The ambassador of Spain to the Russian Empire Anibal Morillo y Pérez del Villar and his “Memories” - T. Yu. Vepretskaya (Ибероамериканские тетради)
The article examines the  memoirs of a Spanish diplomat Anibal Morillo and Perez del  Villar, the   Count of  Cartagena. He  held  the   post of the  Spanish ambassador in the  Russian  Empire in 1914-1916 when World War  One  broke out.  “Memories  of my Embassy in Russia”  by Morillo is a specific source that shows the  life of the  zarist court and diplomatic circles of St. Petersburg in that period. The Count of Cartagena’s activity has not been considered much  in Russian  historiography.  Based on the analysis of his memoirs, the author of the article suggests that Morillo considered the  Russian revolution to be brought in from outside. A study of the  memoirs showed that the  Spanish ambassador at St. Petersburg preferred  German diplomacy and had a peculiar notion of  the  role of Russia  in unleashing the  war.  The  author of this  article concludes that Morillo’s ideas were partly shaped by the  internal problems and the international situation of his own country at the beginning of the 20th century and that the  Spanish ambassador  was one of  the  Spanish Germanophiles. Spain maintained strict  neutrality throughout the  war. The  Spanish embassy  in Russia  carried out  important humanitarian mission  and active mediation activities, supporting Russian  citizens on enemy territory and trying to improve the  situation of Russian  prisoners of war and facilitate their return. The issue of the  personal participation of Anibal Morillo in mediation is also  touched upon in this article.